Live Streaming, Cash on Delivery, dan E-Trust Serta Pengaruhnya terhadap Keputusan Pembelian Impulsif Pengguna Shopee di Kota Pekanbaru - Gemilang Efendi, Bintang; Hayani, Nurrahmi (MUI Kota Pekanbaru, 2024)
This study aims to determine the effect of live streaming, cash on delivery, and e-trust on the impulse purchase decisions of fashion products by shopee users in the Pekanbaru. This type of research is quantitative research using multiple linear regression methods. The number of samples in this study were 96 respondents who were selected using a purposive sampling method. Data collection was carried out by distributing questionnaires to respondents. Research data were analyzed using the SPSS V.25 program. The results of this study show that partially live streaming, cash on delivery, and e-trust have a positive and significant effect on the impulse buying purchase decisions of fashion products by shopee users in the Pekanbaru city. Simultaneous test results show that live streamimg and e-trust have a positive and significant influence on the impulse buying purchase decsions of fashion products by shopee users in the pekanbaru. Cash on Delivery have a positive and significant influence on the impulse buying purchase decsions of fashion products by shopee users in the pekanbaru. The R Square value is 0,285 or 27,5%, indicating that the live streaming, cash on delivery, and e-trust variables as a whole have an influence of 27,5% on the impulse buying intention variable. While the remaining 72,5% is influenced by other variables not examined in this study.